Development and validation of the Thai version of MNREAD acuity charts - Thidarat Leeungurasatien; Songporn Srinut; Yonlada Duenpen; Apichat Tantraworasin (Indian Journal of Ophthalmology)
Purpose: To develop and validate MNREAD acuity charts in the Thai language (MNREAD-TH). Methods: In total, 180 Thai sentences were generated using words specific to the primary 1–3 students. Each sentence contained 60 characters divided into three lines with even left and right margins and was evaluated by instructors in the education program in Thai. The selected 118 sentences were tested in 20 adults and 20 children by measuring reading time and recording the errors. Sentences with extremely high or low mean reading speeds were excluded. The remaining sentences were selected for contributing to the MNREAD-TH charts. For validation, the charts were tested in another 20 normal-sighted adult groups. Results: In total, 118 sentences were tested on 20 adults (range: 23–58 years) and 20 primary school students (age: 8–9 years). The mean (SD) reading speeds in adult and children’s groups were 134.09 (12.45) and 71.33 (10.77) words/min (wpm), respectively. After removing the sentences that deviated by ±1 SD from the mean reading speed, repeatedly had difficulty words, and had low subjective scoring, 60 matched sentences between the groups were selected to develop three versions of the MNREAD-TH chart. The intraclass correlation coefficients between charts were 0.85 for reading acuity, 0.94 for maximum reading speed, and 0.79 for critical print size. Conclusion: The MNREAD-TH charts can be reliably used for evaluating reading performance in Thai people for both children and adults with either normal sight or low vision. These charts are standardized and helpful in clinical trials involving reading.